Aliansi Laki-laki Baru dan Upaya Meredefinisi Peran Gender melalui Kampanye #KitaMulaiSekarang - Abrianthy, Elisabeth Garnistia; Syauki, Wifka Rahma (Tuturlogi: Journal of Southeast Asian Communication, 2021)
Gender inequality has long been a central issue in global social discussions, and Indonesia is no exception. In many circumstances, working women are required to fulfill dual roles in society. On one hand, they are expected to contribute economically, but on the other, traditional expectations compel them to remain as household caretakers. This dual burden can be physically and mentally taxing. Fortunately, organizations like the New Men's Alliance are taking proactive steps to address this inequality. Through the #WeStartNow campaign, they aim to redefine gender roles in society, especially regarding domestic responsibilities. In this context, the research objective is to analyze how the New Men's Alliance, via their Instagram account @lakilakibaru, portrays and interprets gender equality. Specifically, the study focuses on how the visuals and narratives presented reflect the organization's views and aspirations concerning gender equality in Indonesia. The research method employed is Roland Barthes' semiotics, as it offers a deep analytical lens to comprehend the message conveyed by the #WeStartNow campaign. Based on the findings, the #WeStartNow campaign video depicts domestic work in a more positive light when performed by men. However, findings also suggest criticism that when men engage in domestic tasks, it seems more of a romantic gesture than a role-sharing with women, raising further questions about the campaign's effectiveness in genuinely raising awareness about gender equality